Added value recyclability of glass fiber waste as photo-oxidation catalyst for toxic cytostatic micropollutants - Nechifor, Gheorghe; Totu, Eugenia Eftimie; Nechifor, Aurelia Cristina; Constantin, Lucian; Constantin, Alina Mirela; Carausu, Mihaela Elena; Isildak, Ibrahim (NATURE PORTFOLIO, 2020)
There is an increased interest in recycling valuable waste materials for usage in procedures with high added values. Silica microparticles are involved in the processes of catalysis, separation, immobilization of complexants, biologically active compounds, and different nanospecies, responding to restrictive requirements for selectivity of various chemical and biochemical processes. This paper presents the surface modification of accessible and dimensionally controlled recycled silica microfiber with titanium dioxide. Strong base species in organic solvents: methoxide, ethoxide, propoxide, and potassium butoxide in corresponding alcohol, activated the glass microfibres with 12-13 mu m diameter. In the photo-oxidation process of a toxic micro-pollutant, cyclophosphamide, the new composite material successfully proved photocatalytic effectiveness. The present work fulfills simultaneously two specific objectives related to the efforts directed towards a sustainable environment and circular economy: recycling of optical glass microfibers resulted as waste from the industry, and their usage for the photooxidation of highly toxic emerging micro-pollutants.
Keywords: TIO2 NANOPARTICLES; CYCLOPHOSPHAMIDE; DEGRADATION; WATER; IFOSFAMIDE; PHOTOCATALYSTS; NANOCOMPOSITES; 5-FLUOROURACIL; KINETICS; UV/H2O2; Science & Technology - Other Topics